FINANCING THE SUSTAINABLE DEVELOPMENT OF THE LIVESTOCK SECTOR (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, scientific proposals and recommendations on innovative infrastructure development have been developed that serve the livestock sector for further sustainable development. This activity is scientific research and development or production.It is created as a result of the use of best practices for the purpose of modernization and market capture.Production efficiency increases as a result of innovative development of the livestock industry, and in order to accelerate this process, it is necessary to provide socio-economic conditions that encourage the use of new means of development and intensification. Also, in the article the main directions of the sphere of livestock services and the conceptual direction on innovative development of animal husbandry are developed.